2007
DOI: 10.1177/0891988707308806
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-Behavioral Profiles of Neurodegenerative Dementias: Beyond Alzheimer's Disease

Abstract: The neurocognitive and behavioral profiles of vascular dementia and vascular cognitive impairment, dementia with Lewy bodies and Parkinson's disease with dementia, and dementia syndromes associated with frontotemporal lobar degenerations are compared and contrasted with Alzheimer's dementia (AD). Vascular dementia/vascular cognitive impairment is characterized by better verbal memory performance, worse quantitative executive functioning, and prominent depressed mood. Dementia with Lewy bodies and Parkinson's d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 154 publications
(401 reference statements)
2
54
1
1
Order By: Relevance
“…Thus, despite the lack of significant difference between AD and depressed patients, some authors [39,46] were able to differentiate the two conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, despite the lack of significant difference between AD and depressed patients, some authors [39,46] were able to differentiate the two conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, visual impairment such as visuo-spatial, colour and motion perception deficits can be difficult to evaluate in patients with normal routine eye evaluation without the use of specific psychophysics and electrophysiologic exams [39,44,52,54,73,75,77,86]. Thus, it turns to be important the issue on how to evaluate subtle and specific deficits affecting different visual subsystems in AD patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the patient has been bedridden and in the hospital for 3 weeks for a hip fracture and is now being considered for discharge home in a wheelchair, the finding may not be considered abnormal or a contradiction to discharge. However, if the patient is referred to a dementia clinic for work-up and has a history of diabetes and hypertension, this finding in the context of other results might help distinguish vascular cognitive impairment versus Alzheimer's disease (Levy & Chelune, 2007).…”
Section: The Clinical Perspectivementioning
confidence: 91%
“…6 It has been shown that fluctuation in attention is significantly correlated with fluctuation in cognition, and therefore these two characteristics are often assessed together. 7 DLB patients commonly show increased variability in performance on cognitive tasks, both within and between subjects, and when compared with control subjects and subjects with AD. 6 A study by Ballard et al in 2001 8 evaluated attention and fluctuating attention in 85 patients with DLB and 80 with AD, and 35 age-matched controls.…”
Section: Dementia With Lewy Bodiesmentioning
confidence: 99%